DOBC-based frequency & voltage regulation strategy for PV-diesel hybrid microgrid during islanding conditions. (August 2022) - Grover, Himanshu; Verma, Ashu; Bhatti, T.S.
Abstract: The integration of renewable energy sources (RES) based distributed energy resources (DER) lead to reduction in overall system inertia which causes large voltage and frequency fluctuations during any intermittency. This necessitates the integration of fast and robust controllers for low-inertia microgrids. Therefore, this paper proposes disturbance observer based control (DOBC) approach for frequency and voltage regulation of microgrid consisting of solar PV and diesel generator (DG) based hybrid microgrid under islanding situations. The DOBC is included as feed-forward control to the synchronous generator-based DG, which handles the real-time power mismatches and regulates frequency and voltage of islanded microgrid. To demonstrate the operational resilience of the designed controller under real-time uncertainties in PV and load, the controller has been evaluated under the most extreme uncertainty scenarios. The suggested controller has been implemented on a MATLAB/Simulink platform, and results have been validated utilising the real-time simulator OPAL-RT. In addition, the efficacy of the suggested control strategy has been evaluated in the presence of communication delays and noisy load circumstances. Results demonstrate the controller's dynamic performance in regulating the frequency and voltage for low-inertia microgrids. Finally, the proposed control technique has been executed on laboratory-scale microgrid to demonstrate the potential of developed controller. Highlights: Robust auxiliary DOBC for frequency & voltage regulation of PV-Diesel Microgrid. Robust handling of real-time generation & load uncertainty through polyhedral sets. Performance verification in presence of communication delay & noisy load conditions. Real-time testing on OPAL-RT & hardware implementation on lab-scale microgrid setup.